Shaping Ability of Reciproc, UnicOne, and Protaper Universal in Simulated Root Canals - Etevaldo Matos Maia Filho; Cláudia de Castro Rizzi; Matheus Bandeca Coelho; Sara Freitas Santos; Luzia Mayanne Oliveira Costa; Ceci Nunes Carvalho; Rudys Rodolfo de Jesus Tavarez; Janir Alves Soares (The Scientific World Journal)
The study aimed to compare the shaping effects, preservation of the original curvature, and transportation of the apical foramen of Reciproc (VDW, Munich, Germany), UnicOne (Medin, Nové Město na Moravě, Czech Republic), and Protaper Universal (Dentsply Maillefer, Ballaigues, Switzerland) in simulated root canals. Thirty resin blocks with simulated curved root canals were distributed into three groups (n=10), and prepared using Reciproc (RCp), UnicOne (UnO) and the Protaper Universal (PTu). Standardized photographs were taken before and after the instrumentation, after which they were superimposed. Measurements were taken of the quantity of resin removed from the inner and outer walls of the curvature at 6 levels, the curvature angles before and after instrumentation, and the transportation of the apical foramen. RCp obtained the highest values for amount of resin removed from the inner wall while UnO demonstrated similar shaping on both the inner and outer walls. PTu produced the greatest transportation of foramen when compared to the reciprocating instruments. There was no significant difference between the groups in terms of the change in angle (P>0.05). All the instruments were capable of maintaining the original curvature of the root canal; however, the UnO, which used reciprocating movement, produced more conservative shapes with lower foramen transportation.